The relationship between smartphone addiction and fear of missing out: phubbing as the mediator in students at a university’s faculties - Pirincci, Edibe; Karaçorlu, Fatma Nur; Kaya, Mehmet Onur (My University, 2024)
Background: Smartphone addiction is a public health problem. The aim of this study was to investigate the relationship between smartphone addiction with fear of missing out and phubbing. Methods: The universe of this cross-sectional study consisted of all students studying at Fırat University Faculties. 582 students were reached. A questionnaire was used as data collection tools. The questionnaire consists of demographic information form, questions about smartphone use, Smartphone Addiction Scale-Short Version, Fear of Missing Out Scale, and Phubbing Scale. SPSS PROCESS macro version 3.5 (Model 4) was used to test the mediation effect. Results: 51.5% of the students were women and the mean age of all students was 22.06 ± 2.99. Smartphone addiction score was higher in women (p < 0.05). A significant negative correlation was found between smartphone addiction and age (r = -0.10). A significant positive correlation was found between smartphone addiction and daily smartphone usage frequency (r = 0.31) and daily smartphone usage duration (r = 0.44). Fear of missing out and phubbing were significant positive predictors of smartphone addiction. Phubbing had a mediating effect on the effect of fear of missing out on smartphone addiction. Conclusion: Phubbing as a mediator increases the impact of fear of missing out on smartphone addiction.
Keywords: Genel ve Dahili Tıp; Psikoloji